What is queer food? : how we served a revolution - Birdsall, John, 1959- (W. W. Norton & Company, 2025)
"A celebrated culinary writer's expansive, audacious excavation of the roots of modern queer identity and food culture. The food on our plates has long been designed, twisted, and elevated by queer hands. Piecing together a dazzling mosaic of queer lives, spaces, and meals, beloved food writer John Birdsall unfolds the complex story of how, through times of fear and persecution, queer people used food to express joy and build community--and ended up changing the shape of the table for everyone. Tracing the evolution of queer food from the early decades of the twentieth century through the LGBTQ civil rights movement of post-Stonewall liberation and the devastation of AIDS, Birdsall fills the gaps between past and present. He channels the twin forces of criticism and cultural history to propel readers into the kitchens, restaurants, swirling party houses, and buzzing interior lives of James Baldwin, Alice B. Toklas, Truman Capote, Esther Eng, and others who left an indelible mark on the culinary world from the margins. Queer food, as Birdsall brilliantly reveals, is quiche and Champagne eleganza at Sunday brunch and joyous lesbian potlucks in the bunker world of Cold War homophobic purges. It's paper chicken for the gender-rebel divas of Chinese opera in San Francisco, Richard Olney's ecstatic salade composée, and Rainbow Ice-Box Cake from Ernest Matthew Mickler's White Trash Cooking. It's the intention surrounding a meal, the circumstances behind it, the people gathered around the table. With cinematic verve and delicious prose, What Is Queer Food? is a monumental work: a testament to food's essential link to modern queerness that reveals how, like fashion or pop music, cooking and eating have become a crucial language of LGBTQ+ identity. By reframing our understanding of both food and queerness, it opens the door for courageous reckoning and boundless conversation"--